Frequency reconfiguration mechanism of a PIN diode on a reconfigurable antenna for LTE and WLAN Applications - Mohd Shah, Shaharil; Daud, M. F. M.; Zainal Abidin, Zuhairiah; Che Seman, Fauziahanim; Hamzah, Shipun Anuar; Katiran, Norshidah (Institute of Advanced Engineering and Science, 2018)
Microstrip patch antennas are increasingly gaining popularity for usage in portable wireless system applications due to their light weight, low profile structure, low cost of production and robust nature. The patch is generally made of a conducting material such as copper or gold and can take any possible shapes, but rectangular shapes are generally used to simplify analysis and performance prediction. Microstrip patch antenna radiates due to the fringing fields between the patch edge and ground plane. In this work, a frequency reconfigurable antenna with a BAR63-02V Positive-Intrinsic-Negative (PIN) diode is designed, simulated and fabricated. The antenna operates at 2.686GHz for Long-Term Evolution (LTE2500) and 5.164GHz for Wireless Local Area Network (WLAN) applications. In the OFF state, the antenna operates at 5.302GHz, which is also suitable for WLAN application. The proposed antenna is fabricated on a FR-4 substrate with a relative dielectric constant, εr of 4.5, thickness, h of 1.6mm and loss tangent, tan δ of 0.019. The fabrication process is carried out at the Advanced Printed Circuit Board (PCB) Design Laboratory in UTHM.